Development of Graphene Based Field Effect Transistor (FET) - Yacob, Muhammad Zulkhairol (Universiti Teknologi PETRONAS, 2017)
he electronic and electrical properties of graphene have great potential for electronic devices in future. Researchers and engineers exploiting the benefit of graphene to be replaced or integrated together with current electronic device and semiconductor, thus allow more smaller and faster electronic. It could be material that could break Moore’s Law limitation that predicts in 2021 the semiconductor fabrication feature size of electronic devices such as short channel length and width will stop shrinking. In this report, the fabricate and characterize graphene in FET (became Graphene based Field Effect Transistor, GFET) on silicon wafer are demonstrated. There were two design of GFET which is with Al2O3 material and SiO2 uses as insulator to separate drain, source and gate by using atomic layer deposition (ALD) technique. By using all maximum capability of facilities in UTP, I will be able to fabricate (GFET) and characterized the properties.